Biometric recognition : 14th Chinese Conference, CCBR 2019, Zhuzhou, China, October 12-13, 2019, Proceedings /: 14th Chinese Conference, CCBR 2019, Zhuzhou, China, October 12-13, 2019, Proceedings. (2019) - Unknown
No abstract available